D’une commémoration à l’autre. La Bataille d’Ayacucho dans la mémoire et les relations colombo-péruviennes, 1824-1974 - Roger Pita; Daniel Emilio Rojas (Nuevo mundo - Mundos Nuevos)
This article explores the memorial and political stakes surrounding the commemoration of the Battle of Ayacucho (1824), emphasizing its importance as a republican symbol and a site of both national and transnational memory. By focusing on three key historical moments – the immediate celebration, the centenary, and the sesquicentennial – it illustrates how the memory of the battle has been reinterpreted within the national narratives of Colombia and Peru, shaped by political and diplomatic needs. The text also highlights how memorial issues have intertwined with international tensions arising from border conflicts at various points during the 19th and 20th centuries.